Study of the prevalence of morphological varieties of cleft lip and palate in a tertiary medical center - José Fernando Polanski; Bruno Saty Kliemann; Emanuelly Freyhardt; Rita de Cassia Tonocchi; Renato da silva freitas (Revista Brasileira de Cirurgia Plástica, 2020)
Introduction: To verify the prevalence, in a specialized medical center, of the different morphological varieties of orofacial clefts and classify them with details of the affected anatomical structures. Methods: Observational, cross-sectional, retrospective study, based on a review of medical records of children born between 1989 and 2014 who had some kind of cleft lip and/or palate. The type of cleft was analyzed regarding the incisive foramen. Besides, details on the involvement of the lip, dental arch, nasal filter, soft palate, and/or hard palate and uvula were also collected. Results: 1078 medical records of patients with cleft lip and palate were analyzed. When comparing genders, in females, there was a predominance of post-foramen cleft (16.7%), while in males, trans-foramen was more prevalent (25.2%). Separating the cleft as unilateral or bilateral, unilateral ones appeared in more than 75% of patients. Regarding the pre, post, and trans-foramen position, the first two appeared similarly, about 30% each, while the trans-foramen appeared in about 40%. As for the side, the unilateral slits on the left were predominant in both sexes (62% of the unilateral ones). Regarding the anatomical details of the structures involved, the most common injuries were those that involved from the lip to the soft palate. Conclusion: The most prevalent type of cleft was unilateral trans-foramen. In the female gender, the post-foramen cleft, and in the male, the transformation was the most frequent. Unilateral fissures were more common than bilateral fissures, and when unilateral, there was a predominance of lesions on the left.